Lowering IceCube's energy threshold for point source searches in the Southern Sky - Aartsen, M. G.; Abraham, K.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Golup, Geraldina Tamara; Wallace, A.; Wallraff, M.; Wandkowsky, N.; Weaver, Ch.; Wendt, C.; Westerhoff, S.; et al. (IOP Publishing, 2016)
Fil: Aartsen, M. G.. University of Adelaide; Australia